Elderly Muslims, Mosques and Restrictions on Worship: Cognitive Responses in the Covid-19 Red Zone - Damayanti, Poppi; Rahmat, Ihsan; Oktavia, Vira (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2024)
Even though Indonesia has passed Covid-19, there are still various experiences on the ground that need to be uncovered. Many previous studies have discussed the relationship between mosques as places of worship that are considered resistant to Covid-19 restricting policies. Unfortunately, how elderly Muslims react as restriction policy-breaking subjects has not been elucidated. This article aims to explain elderly Muslims' cognitive response to restriction policy in Al- Mukmin and Asy-Syifa mosques, Bengkulu City, which are always in red zone. These two sample mosques are adjacent to the main referral hospital for Covid-19 patients in Bengkulu Province. Qualitative methods were used. Data were collected through interviews, observation and documentation. Triangulation techniques and sources were used to test the validity of the data. The results showed that cognitively, elderly Muslims know, understand, apply, critique, combine with basic knowledge and evaluate the rules. The combination with prior knowledge of older Muslims is considered to be the most urgent stage for the emergence of resistant views and behaviour towards the rules. This finding has implications for government policy in critical times - not just limited to Covid-19 - to provide the same decision at the socio-economic level of society. It was felt that village government should include religious leaders in implementing central government policy.